Guidance with making Batik Training Strategy together with Foreigner to Develop the Student Multicultural Awareness and Global Diversity Character - Nailufar, Ghina; Suherman, Suherman (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2022)
Multicultural awareness and global diversity character is a person’s ability to see, evaluate and interpret the diversity in their life internally and externally, so people able to respect, tolerant and aware of cultural values both our own cultures and foreigner cultures. This study aims to increase student’s multicultural awareness and global diversity character. This training consist of three phases, namely: 1) cultural exchange interaction phase, 2) making batik training phase, 3) activity result and reflection analysis. This study is collaborating with batik teacher, school counselor and school counselor foreign colleague and using some batik tools series as media. This research subjects consist of 6 students of 12 grades in majoring creative craft, batik and textiles for the academic year 2022/2023. The results of narrative research generally show that guidance with batik training strategy with foreigner able to develop the student multicultural awareness and develop their global diversity character. This can be seen in the student excitement, impressions, unique experiences and students understanding of cultural values from batik philosophy. Interaction between local and foreign languages, cultures as well as batik training activities can develop a student’s insight into multicultural awareness and expected to become students who are aware of the importance of global diversity character.